Cryogenic ion trap vibrational spectroscopy of the microhydrated sulfate dianions SO42−(H2O)3−8. Issue 47 (26th November 2020) - Knorke, Harald; Li, Huiyan; Warneke, Jonas; Liu, Zhi-Feng; Asmis, Knut R.
Abstract : Infrared photodissociation spectra of microhydrated sulfate dianions with three to eight water molecules are presented over a broad spectral range that covers intramolecular solvent and solute modes as well as intermolecular librational modes. Abstract : Infrared photodissociation spectra of the D2 -tagged microhydrated sulfate dianions with three to eight water molecules are presented over a broad spectral range that covers the OH stretching and H2 O bending modes of the solvent molecules at higher energies, the sulfate stretching modes of the solute at intermediate energies and the intermolecular solute librational modes at the lowest energies. A low ion temperature combined with messenger-tagging ensures well-resolved vibrational spectra that allow for structure assignments based on a comparison to harmonic and anharmonic IR spectra from density functional theory (DFT) calculations. DFT ab initio molecular dynamics simulations are required to disentangle the broad and complex spectral signatures of microhydrated sulfate dianions in the OH stretching region and to identify systematic trends in the correlation of the strength and evolution of the solute–solvent and solvent–solvent interactions with cluster size. The onset for the formation of the second solvation shell is observed for n = 8.